Dynamics of factor of 137Cs accumulation by fishes of I - II trophic levels in case of radionuclide concentration variation in water of freshwater bodies - V. V. Belyaev; E. N. Volkova (Ядерна фізика та енергетика)
Behaviour value of factor of accumulation 137Cs by non-predator species of fishes in case temporal increase of concentration of radionuclide in water of freshwater bodies was explored by the methods of mathematical modeling. It has been stated that probability of difference between instantaneous and equilibrium values of factor of accumulation in case of single increase concentration of 137cs in water.